Evaluation of Teacher Learning Methods for Student Empowerment in Elementary Schools - Asfa Atiyah; Rusdiana Navlia (Penerbit Presisi Pustaka, 2025)
The focus of the evaluation of learning methods is on assessing the effectiveness of the learning strategies or techniques applied by teachers in delivering learning materials, and is also used to analyze the impact on the empowerment of elementary school students. This study aims to analyze how the learning methods applied by teachers can influence students’ activeness, motivation, discipline, self-confidence, contribution and participation, and cooperation in groups during the learning process. The learning methods applied must be adapted to the diverse needs of students. Therefore, an evaluation of learning methods aims to determine which methods are appropriate and equivalent, comprehensive, and sustainable. This study uses a literature review method by collecting data from books, journals, and other scientific works related to the discussion theme. The research analysis shows that the application of learning methods such as Synergetics, Exemplary, Think-Pair-Share, Collaborative Learning, Inquiry, and Participatory Learning has a positive impact on the development of knowledge, skills improvement, communication, and student cooperation. This research can be used by teachers as a guide in determining and implementing learning methods that are appropriate to student needs in order to strengthen student empowerment to become more responsible, independent, critical, and positive individuals in school.